Clement Greenberg e la Halakah del Modernismo - Camilla Froio (Aisthesis, 2016)
The understanding of the meaning of Jewish identity in Clement Greenberg's work follows the deep relationship between the conception of Modernism and the interpretation of Franz Kafka's short story The Great Wall of China. Greenberg, whose role as one of the first american popularizers of Kafka's narratives has been relevant, ascribes to the bohemian author an halachic reasoning closely related to his jewish origins. This strictly firm and normative mindset finds resemblances in Greenberg's modernist theory and critical practice, which, according to Susan Noyes-Platt's study, could be interpreted as a derivation, in many aspects, of his Jewish origins and, particularly, as the critic's need to preserve his intellectual thinking from the nazi-fascist advance. Moreover, the article proposes to interpret Greenberg's purism as a form of messianism, that is a faith in a future, but indefinitely belated, absolute purification of the medium.